2022
DOI: 10.3390/jcm11206046
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Quality of Endodontic Treatment in Patients with Cardiovascular Disease and Associated Risk Factors

Abstract: This study aimed to determine the prevalence and quality of endodontic treatment, by radiographically assessing the periapical periodontitis and endodontic treatment status in patients with cardiovascular disease (CVD) and cardiovascular risk (CVR) factors. Patients who visited the Out Patient Department of Institute of Dental Sciences and Department of Cardiology, Institute of Medical Sciences and SUM Hospital, Siksha ‘O’ Anusandhan University, Bhubaneswar, from August 2021 to February 2022, for a check-up or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…The higher prevalence of systemic alterations in females may be attributed to their increased health awareness and higher utilization of medical and dental care. 20 A higher prevalence of comorbidities in males was found in patients undergoing endodontic treatment 22 and periodontal treatment 23 , likely due to the inclusion of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher prevalence of systemic alterations in females may be attributed to their increased health awareness and higher utilization of medical and dental care. 20 A higher prevalence of comorbidities in males was found in patients undergoing endodontic treatment 22 and periodontal treatment 23 , likely due to the inclusion of elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, systemic diseases linked to inflammation may impair crucial immune factors involved in the pathogenesis of apical periodontitis, 27 potentially impacting the outcome of the treatment. Most acquired CVD are associated with increased systemic inflammatory burdens, which can lead to adverse outcomes in endodontic therapy, 28,29 and may be a risk factor for treatment failure. 30 However, Laukkanen et al 31 found that CVD did not have a significant effect on the success rate of endodontic therapy.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…La ECV engloba trastornos que afectan el corazón y el sistema vascular, abarcando diversas condiciones como la cardiopatía coronaria (CHD), la enfermedad arterial periférica y la enfermedad cerebrovascular (Segura-Egea et al, 2023). Entre las afecciones cardiovasculares más frecuentes en pacientes que buscan atención dental se encuentran la ECV, la hipertensión (HTA), las arritmias, la endocarditis infecciosa y la insuficiencia cardíaca (Dash et al, 2022).…”
Section: Enfermedades Cardiovasculares (Ecv)unclassified
“…Las enfermedades sistémicas más comunes a nivel global incluyen la diabetes mellitus (DM), la hipertensión arterial, las enfermedades cardiovasculares, los accidentes cerebrovasculares, las enfermedades autoinmunitarias y el hábito de fumar (Dash et al, 2022). Los pacientes con enfermedades sistémicas crónicas se asocian con frecuencia a problemas y enfermedades de la salud oral, provocando alteraciones en las células sanguíneas y los mediadores de la inflamación, lo cual afecta a la respuesta reparadora del tejido e incluso puede mantener el proceso inflamatorio y la resorción ósea periapical después de haber finalizado el tratamiento de conducto (RCT) (Michael & Edgar, 2012b) .…”
Section: Introductionunclassified